Stability Properties of Positive Solutions to a Quasilinear Elliptic Equation Involving the p-Laplacian and Indefinite Weight: Ghasem A. Afrouzi, Saleh Shakeri - Team, Support (Thai Journal of Mathematics, 2017)
In this note, we discuss the stability and instability results of positive solutions the following reaction -diffusion equation equation1 {arrayll -Δ_p u=m(x)u^p-1-u^γ-1-ch(x) & in Ω, Bu=0 & on Ω